PEMBUATAN MINUMAN HERBAL “TEH SECANG” UNTUK MENINGKATKAN KESEHATAN DAN PEREKONOMIAN MASYARAKAT DESA TANJUNG TAMBAKREJO BOJONEGORO - Ari Abi Aufa (Mafaza : Jurnal Pengabdian Masyarakat, 2021)
Covid 19 has changed various orders in social life. Human beings, who are actually social creatures, are prevented from interacting each other, which results in obstructing efforts to fulfill the basic needs of human life. People must adjust the way they interact with each other to avoid the possibility of contracting Covid 19. But on the other hand, people still have to work to make ends meet for themselves and their families. The community of Tanjung Tambakrejo Bojonegoro village cannot be separated from the impact of Covid 19. This social service uses the ABCD method, which is service that focuses on the use of assets owned by the village to improve their lives. The existing assets in these areas are sometimes neglected and not fully utilized by the local community due to their ignorance. Therefore, this method is taken to reintroduce existing assets in the community so that they can be used to improve their lives. Based on the survey conducted, it was found that various vegetable assets have not been maximally utilized, one of which is Caesalpinnia sappan L. Through various research conducted, it turns out that Caesalpinnia sappan L can be used as a warm drink that is both delicious and healthy. Based on this, the people of Tanjung village were then taught how to make herbal drink made from Caesalpinnia sappan L, and how to sel it online to improve their health and also their economy.